The number of passively smoked cigarettes and the risk of lung cancer among the inhabitants of the Lubelskie Region (2013-2017) - Chudzik, Robert; Rybojad, Beata; Rybojad, Paweł (Journal of Education, Health and Sport, 2020)
According to WHO, clean air is considered as one of the basic criterion influencing human health. Airborne particulate matters (PM) 2,5 are mixtures of organic and inorganic particles smaller than 2.5 µm. They have broad negative effect on health especially on respiratory and cardiovascular system. They could increase the sensitivity to air ways infections, worsen: allergic diseases, hypertension, myocardial infarction and also increase the risk of neoplastic diseases. NO2 pollution arises mainly during burning of fossil fuels, which is mainly related to road transport. On the basis of numerous scientific research, it is believed that the long term exposure to NO2 could increase inflammation and eventually lead to higher cancer morbidity. We analyzed the data available in the Polish National Cancer Registry (PNCR), Chief Inspectorate for Environmental Protection and Air Quality Guidelines, We checked air pollution by the means of PM2.5and NO2 and thanks to mathematical equation delivered by Saskia C. van der Zee converted them into number of passively smoked cigarettes. Above data we compared to lung cancer morbidity in Lubelskie Region. Based on the latest available data and literature, we can conclude that in 2013-2017 each inhabitant of Lubelskie Region smoked average 8 cigarettes a day +/- 2. The incidence of lung cancer is more or less the same number. After 75 years everyone in the exanimated region had 30 package-years of passive smoking and high risk of lung cancer. Over same period of time cumulative risk of lung cancer according to PNCR were in women almost 2% and in men almost 6% Air quality in Poland is not satisfactory, exceeding the standards presented in the WHO Guidelines 2005, we can assume that this translates into a high risk of the incidence of lung cancer among our inhabitants.